Synthesis and antimicrobial evaluation with DFT study for new thiazole derivatives - Sumayah Saadi Abbas; Ammar A.Razzak Mahmood Kubba (College of Pharmacy University of Baghdad, 2018)
Two compounds,[2-amino-4-(4-nitro phenyl) 1,3-thiazole],(4) and [2-amino-4-(4-bromo phenyl) 1,3-thiazole],(5), were synthesized by refluxing thiourea (1) with each of  para-ntiro and para-bomophanacyl bromides(2) and (3) respectively, in absolute methanol. Then, by reaction of [5] with 3,5-dinitrobenzoyl chloride in dimethylformamide (DMF) yielded  (6) .On the other hand, reaction of (4) with chloroacetyl chloride in dry benzene afforded (7), which is  upon treatment with thiourea in absolute methanol, afforded (8) . The characterization of the titled compounds were done utilizing FTIR spectroscopy, 1HNMR, CHNS elemental analysis and by measurements of  their physical properties. The synthesized compounds had been screened for their, in vitro  preliminary antimicrobial activity against four Gram positive bacteria (Staph. aureus, Micrococcus luteus, Bacillus subtilis and Bacillus pumilus),  and four Gram negative bacteria (Pseud.aeroginosa, E.coli, Proteus mirabilis and Klebsiella pneumoniae)and three fungi species: (Saccharomyces cerevisiae, Candida Tropicalis and Candida albicans) using a minimum  inhibitory concentration (MIC) of 100 µg\ml of derivative  in dimethylsulfoxide, by  well diffusion method. Compound (6) showed moderate antibacterial activity against some tested Gram positive bacteria (Bacillus pumilus and Bacillus Subtilis) and a moderate antifungal activity towards Candida albicans. Computational study was performed   to calculate some of the thermodynamic parameters of synthesized derivatives by using density functional theory (DFT).